Politik Islam Nusantara Said Aqil Siraj di Media Massa - Ghozali, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This article aims to examine the political thoughts of Islamic Nusantara Said Aqil Siraj in the Mass Media. His various ideas in introducing peaceful, polite and cultured Islamic teaching in accordance with the character of Indonesia society through the mass media received negative attacks from group in the name off Nahdlatul Ulama Garis Lucu, caliphate fighters and religious figures who lost in the 2019 presidential election. Said Aqil Siraj’s open resistance against the onslaught of haters of Islam Nusantara as a from of Islamic politics in order to introduce the essence of Islamic teachings in multicultural, ethnic, tribal and religious society through his thoughts in the mass media. This research takes the form of a research library, namely collecting data related to said aqil siraj’s statements in the mass media, carrying out classification, analysis and drawing conclusions. The research result; first, Islam Nusantara which was developed by Said Aqil Siraj is an Islam that can coexist with culture and needs each other in certain ways. This problem will have implicatiions for the understanding and characteristics of the Indonesian Islamic community in behaving, speaking and behaving according to Indonesian culture wthout giving up their identity as a muslim who is obedient to Allah. Second, Islam Nusantara has implication for the political views of Islam Nusantara, which is Said Aqil Siraj’ strategi to introduce to the public that the Indonesian political system with the ideology of Pancasila and the concept of a Nation State in the form of the Unitary State of the Republic of Indonesia does not conflict with Islamic law.